2009
DOI: 10.1039/b909873a
|View full text |Cite
|
Sign up to set email alerts
|

The dual nature of extracellular ATP as a concentration-dependent platelet P2X1 agonist and antagonist

Abstract: Patient groups subject to higher occurrence of stroke (e.g., people with diabetes, cystic fibrosis, pulmonary hypertension) have reduced release of ATP from their erythrocytes (ERYs) when subjected to flow-induced deformation or pharmacological stimuli. These same groups also have platelets that are more adhesive in comparison to controls. Here we show platelet aggregation, and inhibition of that aggregation, is affected by free Ca(2+) entering the platelet through the ATP-gated P2X1 receptor. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
(58 reference statements)
1
21
1
Order By: Relevance
“…Recently, in vitro studies involving immobilized endothelial cells revealed that C-peptide may also have an effect on platelet adhesion [47]. This finding is in contrast to a previous report that Cpeptide does not have any direct effects on platelets [48].…”
Section: +contrasting
confidence: 56%
See 3 more Smart Citations
“…Recently, in vitro studies involving immobilized endothelial cells revealed that C-peptide may also have an effect on platelet adhesion [47]. This finding is in contrast to a previous report that Cpeptide does not have any direct effects on platelets [48].…”
Section: +contrasting
confidence: 56%
“…However, recently, our group has demonstrated that ATP does indeed participate in platelet activity. In fact, it was shown that below normal levels of ATP binding to the P2X receptor resulted in a decrease in NO production by platelets, resulting in an increase in platelet aggregation [47]. However, as ATP levels increased, both the NO production and aggregation rates of platelets decreased.…”
Section: C-peptide: a Multi-tasking Molecule Or Stimulus Of Such?mentioning
confidence: 99%
See 2 more Smart Citations
“…Current efforts, some described here, are also attempting to provide evidence that the RBC may be a determinant in platelet function via ATP binding to platelet receptors [46]. Other results demonstrate that the RBC may be serving as a mediator of drug efficacy [44]. lar levels of ATP in the RBC).…”
Section: The Rbc As a Determinant Of Platelet Functionmentioning
confidence: 83%